2004
DOI: 10.1366/000370204773580176
|View full text |Cite
|
Sign up to set email alerts
|

Development of Infrared Electroabsorption Spectroscopy and its Application to Molecular Structural Studies

Abstract: We have constructed an infrared electroabsorption spectroscopic system employing the alternating current (AC) coupled dispersive method developed previously in our laboratory. It is highly sensitive, measuring electric-field-induced infrared absorption changes as small as 6 x 10(-8) in the mid-infrared region of 4000-820 cm(-1). Infrared electroabsorption spectra of liquids and solutions can be measured at room temperature. The system was first applied to liquid acetone to observe the orientational as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 39 publications
1
56
1
1
Order By: Relevance
“…11,12 In solution, on the other hand, molecules are easily reoriented and the fieldinduced reorientation can be detected by the EA measurements. [13][14][15] However, the precise measurements of the EA spectra in solution are not so easy due to the difficulty in application of strong electric fields to solutions.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In solution, on the other hand, molecules are easily reoriented and the fieldinduced reorientation can be detected by the EA measurements. [13][14][15] However, the precise measurements of the EA spectra in solution are not so easy due to the difficulty in application of strong electric fields to solutions.…”
Section: Introductionmentioning
confidence: 99%
“…18 An IR detection technique with very high sensitivity allowed the measurement of the effect of electric field on molecules by infrared spectroscopy. 19 Time-and space-resolved Raman microscopic studies, initially of yeast and of live plant and animal cells, revealed the 'Raman spectroscopic signature of life at 1602 cm 1 ', which clearly reflects the metabolic activity of mitochondria. 20 Hamaguchi thinks that this band serves as a useful marker for the physiological activity of each cell, or even of life itself.…”
Section: Return To the University Of Tokyomentioning
confidence: 99%
“…On the basis of Eqs. (1) and (2), the change in absorbance under the influence of an external field for an isotropic, immobilized sample can be quantitatively expressed as [1,4,5,11] with…”
Section: Theorymentioning
confidence: 99%
“…Although infrared Stark spectra have been reported for small molecules [2][3][4][5], proteins [6], and polypeptide [7,8], the number of samples measured is limited. It results from the difficulty in the measurements of infrared Stark spectra.…”
Section: Introductionmentioning
confidence: 99%